Comparatively profiling the transcriptome of human, Porcine and mouse oocytes undergoing meiotic maturation - Naru Zhou; Xin Wang; Yi Xia; Zongliang Liu; Lei Luo; Rentao Jin; Xianhong Tong; Zhenhu Shi; Zhichao Wang; Heming Sui; Yangyang Ma; Yunsheng Li; et al. (BMC Genomics, 2025)
Abstract Background Oocyte maturation is a critical process responsible for supporting preimplantation embryo development and full development to term. Understanding oocyte gene expression is relevant given the unique molecular mechanism present in this gamete. Comparative transcriptome analysis across species offers a powerful approach to uncover conserved and species-specific genes involved in the molecular regulation of oocyte maturation throughout evolution. Results Transcriptome analysis identified 4,625, 3,824, 4,972 differentially expressed genes (DEGs) between the germinal vesicle (GV) and metaphase II (MII) stage in human, porcine and mouse oocytes respectively. These DEGs showed dynamic changes associated with oocyte maturation. Functional enrichment analysis revealed that the DEGs in all three species were mainly involved in DNA replication, cell cycle and redox regulation. Comparative transcriptome analysis identified 551 conserved DEGs in the three species with significant enrichment in mitochondria and mitochondrial intima. Conclusions This study provides a systematic comparative analysis of oocyte meiotic maturation in humans, pigs and mice identifying both conserved and species-specific patterns during oocyte meiosis. Our findings also implied that the selection of oocyte expressed genes among these three species could form a basis for further exploring their functional roles in human oocyte maturation.